DESIGN OF EMPOWERMENT MODEL FOR SMOKED FISH INDUSTRY THROUGH CUSTOMER RELATIONSHIP MANAGEMENT BASED ON THE ADAPTATION OF DIGITAL TRANSFORMATION IN SIDOARJO COAST - Siswati, Endang; Imamah, Nurul; Inayah, Nur Lailiyatul; Kharismawati, Ika (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The aim of this research is to develop smoked fish home industry through customer relationship management and identify supporting factors and also barriers in the development of the smoked fish industry through customer relationship management. This research used a qualitative approach. Data collection was carried out using interviews, observations and focus group discussions consisting of the village head, Bumdes director, and smoked fish industry stakeholders in Penatarsewu village. After the data was obtained, data triangulation was carried out and then analysed, namely data reduction, data presentation and conclusions. The results found that the customer relationship management model in small businesses is applied to services, namely providing good service to consumers and on social media. Marketing is done online and sales are made directly. Sales management organizes the sales' SOP from orders to products received by consumers. Factors that support the development of smoked fish home industry through customer relationship management include high consumer demand and it makes the product always sold out, meaning there is potential to be developed for the better. Meanwhile, the constraining factor is that the ability of resources is still limited, making the smoked fish business in Penatarsewu village rather difficult to develop.